Unveiling Drivers of Environmental Disclosure in Mining: Performance, Profitability, and Size - Indah Maulidiah; Linah Linah; Morinda Silfiora; Ida Rosnidah (International Journal of Management, Accounting and Economics)
This study analyzes the variables influencing environmental disclosure in companies by focusing on company size, profitability, and environmental performance. When descriptive statistical analysis was performed on a sample of 60 companies, the average environmental disclosure score was 0.3246, suggesting that transparency is still lacking and needs to be improved. Data normality was tested using the Kolmogorov-Smirnov method, and no issues of heteroscedasticity were found. The results show that the level of environmental disclosure is negatively influenced by environmental performance, as measured by the PROPER score. While company size, determined by taking the logarithm of total assets, has a positive impact, profitability, as indicated by Return on Assets (ROA), also exhibits a negative effect. According to the report, greater environmental effects are typically associated to larger companies. According to multiple regression analysis, the variable studied only explains 15.2% of the variation in environmental disclosure, indicating that there may be more factors that have not yet been studied. According to these findings, corporate environmental disclosure is crucial for improving a company’s reputation and reducing the information gap between stakeholders and companies.